2013
DOI: 10.1016/j.parkreldis.2012.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Potential reliability and validity of a modified version of the Unified Parkinson's Disease Rating Scale that could be administered remotely

Abstract: Background By permitting remote assessments of patients and research participants, telemedicine has the potential to reshape clinical care and clinical trials for Parkinson disease. While the majority of the motor Unified Parkinson’s Disease Rating Scale (UPDRS) items can be conducted visually, rigidity and retropulsion pull testing require hands-on assessment by the rater and are less feasible to perform remotely in patients' homes. Methods In a secondary data analysis of the Comparison of the Agonist prami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
108
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 121 publications
(115 citation statements)
references
References 13 publications
0
108
0
1
Order By: Relevance
“…Evidence from the literature, however, suggests that a modified version of UPDRS-III without rigidity and retropulsion pull testing administered remotely was reliable and valid [3,4]. This suggests that education regarding the effectiveness of PD assessment via telehealth could help remove barriers to its adoption by allaying patient fears and increasing confidence in the telemedicine program.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence from the literature, however, suggests that a modified version of UPDRS-III without rigidity and retropulsion pull testing administered remotely was reliable and valid [3,4]. This suggests that education regarding the effectiveness of PD assessment via telehealth could help remove barriers to its adoption by allaying patient fears and increasing confidence in the telemedicine program.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that assessment of motor impairment in PD via telehealth is feasible, valid, and reliable [3,4]. Randomized clinical trials (RCTs) have shown that telemedicine programs for PD care could be feasible, cost-effective, and provide clinical benefit equivalent to that of traditional in-person care [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The motor portion (part III) of the scale was modified to exclude assessments of rigidity and balance, which cannot be assessed remotely. 23 Additional assessments included changes in the 15-item Geriatric Depression Scale, the Montreal Cognitive Assessment, the European Quality of Life Five Dimension Five Level Scale, and the Patient Global Impression of Change. Patient and clinician satisfaction, as well as hospitalizations and emergency department visits, were evaluated by survey after each visit.…”
mentioning
confidence: 99%
“…With timely monitoring, many of these adverse effects are reversible through reduction or cessation of medication [7]. As PD progresses, loss of mobility can cause clients to become bedridden or confined to a wheelchair, increasing the difficulty of travelling to medical appointments [8]. …”
Section: Introductionmentioning
confidence: 99%
“…Abdolahi et al (2013) conducted a study to compare whether administering the UPDRS without the items that require physical interaction would make a significant difference to trial outcomes [8]. Modified UPDRS scores, which exclude the rigidity and postural stability testing items, were compared to the standard UPDRS [8].…”
Section: Introductionmentioning
confidence: 99%